2012
DOI: 10.4038/tar.v23i1.4631
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sustainability of Community Water Supply Projects in Kandy District

Abstract: Introduction of community water supply projects, implemented and managed by the community with an initial support from governments or international organizations has been considered as a useful strategy to provide access to safe drinking water to rural communities. Sri Lanka has also adopted this strategy through the Community Water Supply & Sanitation Project. Since there were concerns about the sustainability of numerous water schemes implemented throughout the country, a research was carried out in 20 commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 3 publications
(1 reference statement)
1
11
0
Order By: Relevance
“…For instance, in a multi-country study that covered Bolivia, Peru and Ghana, Whittington et al (2009) reported that rural water utilities substantially improved billing accuracy, revenue collection efficiency, and reduced unaccounted for water, which in turn, enabled the utilities to eliminate water rationing. Similar findings appear in the outputs of studies conducted by Check (2015); Abebe, Bosona and Gebresenbet (2013); Adank and Tuffuor (2013), Mimrose andGunawardena (2011), Fragano (2010) and World Bank (2006), among others. Details are highlighted under the literature review section.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…For instance, in a multi-country study that covered Bolivia, Peru and Ghana, Whittington et al (2009) reported that rural water utilities substantially improved billing accuracy, revenue collection efficiency, and reduced unaccounted for water, which in turn, enabled the utilities to eliminate water rationing. Similar findings appear in the outputs of studies conducted by Check (2015); Abebe, Bosona and Gebresenbet (2013); Adank and Tuffuor (2013), Mimrose andGunawardena (2011), Fragano (2010) and World Bank (2006), among others. Details are highlighted under the literature review section.…”
supporting
confidence: 73%
“…In Sri Lanka, Mimrose and Gunawardena (2011) also reported some linkage between financial stability of public water schemes and revenue generation aspects such as efficiency of billing systems, efficiency of revenue collection, non-revenue water as well as unaccounted for water. In Paraguay, Fragano (2010) reported that 67% of water projects involved in the study were consistent in providing services due to financial stability, 54% were in a good state of maintenance, while 29% had either expanded or were in the process of expanding their infrastructural systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…al. 2015;Mimrose et. al, 2012;Giovannoni & Fabietti, 2013;Kyessi & Ka'Bange, 2014;Brown and Heller, 2017. Environmental & Health management abilities; Though informal water supply market is an old urban development phenomenon and has received abundant of jsd.ccsenet.org scholarly rhetoric (Kjellén & McGranahan, 2006;Wutich et.…”
Section: Authorsmentioning
confidence: 99%
“…al., 2004). Cooperation may not only build assets and governance capacities (hydro-technical, socio-social, economic and environmental/health, organisation and institutional) (Mimrose et. al, 2012;Rogers et.…”
Section: Authorsmentioning
confidence: 99%
“…Extant literature reveals that financial sustainability of public water utilities is a function of multiple factors, including financial management practices such as compliance with relevant regulations when procuring goods, services and works (Adank & Tuffuor, 2013); effectiveness of internal control mechanisms in enforcing adherence to expenditure policies (Nankunda, 2013); as well as relevance of activities on which water revenues are spent (Mimrose & Gunawardena, 2011;Wambua, 2004). Other aspects of financial management that influence financial sustainability of public water utilities include efficiency of revenue collection and ability to meet revenue targets, effectiveness of external audit in propagating ideal financial management practices as well as the degree of fiscal discipline, which manifests through the frequency of budget overruns (Adank & Tuffuor, 2013;Mimrose & Gunawardena, 2011;Whittington, Davis, Prokopy, Komives, Thorsten, Lukacs, & Wakeman, 2009).…”
Section: Introductionmentioning
confidence: 99%